2015
DOI: 10.1080/15548627.2015.1108507
|View full text |Cite|
|
Sign up to set email alerts
|

MIR517Cinhibits autophagy and the epithelial-to-mesenchymal (-like) transition phenotype in human glioblastoma through KPNA2-dependent disruption of TP53 nuclear translocation

Abstract: (2015) MIR517C inhibits autophagy and the epithelial-to-mesenchymal (-like) transition phenotype in human glioblastoma through KPNA2-dependent disruption of TP53 nuclear translocation, Autophagy, 11:12, 2213-2232, DOI: 10.1080/15548627.2015 LG, low glucose; MAP1LC3B/LC3B, microtubuleassociated protein 1 light chain 3B; MU, mutation; NC, negative control; NSC, neural stem cell; oe, overexpressing; OS, overall survival; PFS, progression-free survival; qRT-PCR, quantitative real-time reverse transcription polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 56 publications
(63 reference statements)
4
60
0
Order By: Relevance
“…TMZ induces massive DNA damages and triggers cell apoptosis of glioma cells . TMZ was reported to also activate autophagy in U87MG cells . We observed a similar effect as indicated by MDC staining (Fig.…”
Section: Resultssupporting
confidence: 82%
“…TMZ induces massive DNA damages and triggers cell apoptosis of glioma cells . TMZ was reported to also activate autophagy in U87MG cells . We observed a similar effect as indicated by MDC staining (Fig.…”
Section: Resultssupporting
confidence: 82%
“…44 Lu et al found that CQ blocked autophagy-induced cell migration and GBM infiltration. 45 Furthermore, some relevant clinical studies of CQ in the treatment of brain tumor have been reported. In a double-blinded clinical trial involving 30 patients with glioblastoma multiforme (NCT00224978) (a Phase III clinical trial), randomizing eligible patients with surgically confirmed glioblastoma to receive conventional chemotherapy and radiotherapy plus placebo or 150 mg/day CQ per os, the result showed CQ-receiving patients exhibited an imp roved mid-term survival as compared with their control counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the precise mechanism of autophagy and senescence and their interrelationship is important to understand their roles in healthy cells and in disease (Lin & Baehrecke, ; Lecot et al, ). miRNA clusters are likely to regulate autophagy, as they target many autophagy pathway genes such as unc‐51 like autophagy activating kinase 1 ( ULK)1 , TP53 and slu7 homolog splicing factor ( SLU7) (Chen et al, ; Lu et al, ). Ulk1 along with Beclin‐1 , is important for reticulocyte clearance of mitochondria via autophagy‐related protein 5 (Atg5)/Atg7‐independent autophagy (Honda et al, ).…”
Section: Oncogenic and Tumour‐suppressor Mirna Clustersmentioning
confidence: 99%